مدى فعالية نظم المعلومات المحاسبية فيظل التجارة الإكترونية - شداد, أحمد (My University, 2017)
The Effect of the Electronic Trade on Accounting Information High Quality Abstract In the light of developments take place in the world of telecommunication due to the extension of its area in ma-ny economics facets at various levels. One of these phenomena in the electronic trade via internet and its effects on the outputs of the accounting information system especially on the quality of accounting information and here lies the significant of the current research. The objectives of this paper are to define of the accounting process of the electronic trade and its influence on the quality of the accounting information. In order to achieve the a fore-mention of objectives we hypothesize that the electronic trade contributes in promoting the quality the accounting information by sup-porting some of qualification of the accounting information in order to achieve the objectives of and validate its hypothesis a study has been conducted by using the descriptive and analytical ap-proach by adopting a number of References which provide the mechanisms and rules of this approach .the special concept of the accounting information system have been realized and regared as the outputs this system on the quality and qualifications of this information. The electronic trade has its stages of developments and influences on accounting in general and the quality of accounting information in particular and analysing these effects. The research has come to the conclusion that the electronic trade has a positive effect by backing the electronic aspect on the quality of the accounting information.
BADR - محمدية
Keywords: لمعلومات المحاسبية - التجارة الإكترونية